Baby Incubator Monitoring Center for Incubator Temperature and Skin Temperature using WiFi Network - Nuristadarro, Nuristadarro; Hamzah, Torib; Lamidi, Lamidi (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2019)
Premature infants with birth age less than 38 weeks who have a higher risk of death require continuous monitoring. Therefore, a temperature monitoring system is needed in the incubator. So the purpose of this research is to develop a baby incubator monitoring system that still uses the manual method to be faster and easier. This module has a wireless system and uses a Wi-Fi network for data transmission. By using several ESP32 modules assembled into a central system, where the data obtained from monitoring skin temperature from the DS18B20 sensor and incubator temperature monitoring data from the DHT22 sensor will be processed by the ESP32 which functions as a client and collected at one central point of the ESP32 which has been functioned as a server using the wifi network as data transmission. then the data collected on the server will be displayed on the nextion TFT display. Based on the overall measurement results using 2 baby incubators, the highest error value is 1.387% for the incubator temperature parameter and 3.911% for the skin temperature parameter. The results showed that the module that was made still contained errors in each measurement. The results of this study can be implemented to make it easier for nurses to monitor premature babies easily and quickly